Could psychedelics open new doors for science and business? psychedelic medicines and therapies are becoming more mainstream and may offer innovative solutions in an era of declining mental health and well-being - Meister, Alyson; Oppegaard, Kaja; Grotefeld, Eric; Bouquet, Cyril (MIT Sloan Management Review, 2022)
Psychedelic drugs have a history clouded by stigma, but a new wave of clinical research could change how they're perceived and used. Today, a psychedelic renaissance points to potential uses of such drugs in the fields of psychiatry, mental health, and well-being. Some companies have seized upon psychedelics' potential to treat psychological conditions and spur creativity and are making business investments that they hope will pay off in breakthroughs that improve people's lives.
"Reprint 64230."
Keywords: Hallucinogenic drugs -- Therapeutic use; Hallucinogènes; Emploi en thérapeutique; Hallucinogenic drugs; Therapeutic use